Auditory and Visual Contribution to Egocentric Distance and Room Size Perception. Issue 4 (December 2013) - Maempel, Hans-Joachim; Jentsch, Matthias
The perception of rooms involves various unimodal and multimodal aspects on different perceptual levels. Rather abstract yet self-evident aspects are the source distance and the room size. We investigated to what extent the perceived room size and egocentric source distance as supramodal aspects are based on the auditory and the visual modality, i.e. experimentally influenced by the acoustic and optical stimulus. The statistical determination of the respective contributions demands the mutually independent variation of optical and acoustical room properties, usually referred to as conflicting stimulus paradigm. Simulation data of four rooms were collected acoustically by acquiring binaural room impulse responses for different head orientations and optically by acquiring stereoscopic images of the rooms including the electroacoustic sound source. In the laboratory, respective acoustic scenes were played back applying dynamic binaural synthesis, whereas the optical scenes were presented by the use of a stereoscopic display. Test participants were asked to assess the source distance and the room size. Results show main effects of the modalities rather than an interaction effect. It was found that distance perception in rooms is predominantly based on the acoustic stimulus characteristics whereas room size perception predominantly relies on optical information. There is no evidence in favour of the proximity image effect hypothesis. Results do also not confirm an auditory or audio-visual underestimation of the source distance but show a general underestimation of room size and indicate an audio-visual asymmetry regarding the accuracy of room size perception. Maximum accuracy and cross-modal consistency of judgements were distinctively observed in low-absorbent rooms.